Analisis Gharar dan ‘ADL dalam Rantai Pasok Gas Elpiji 3 Kg dengan Pendekatan Maqhasid Syariah di Pangkalan Fawaid Kecamatan Gondanglegi - ahmad isfarhanuddin; roisul adib (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study analyzes the application of the principles of gharar (uncertainty) and ‘adl (justice) in the subsidized LPG supply chain at Pangkalan Fawaid, Gondanglegi District, using the Maqashid Syariah approach. The primary focus of this research is to identify issues related to the distribution of subsidized LPG that involve Islamic economic principles, particularly concerning uncertainty and injustice that may disadvantage the public, especially low-income households. The main issues identified include the uncertainty of distribution schedules, price fluctuations, limited supply, and a lack of transparency in information, leading to unequal access for low-income households. The research employs a qualitative-empirical method with data collection techniques such as in-depth interviews, participatory observation, and document analysis. Five key informants were selected through purposive sampling to provide comprehensive insights into the issues surrounding subsidized LPG distribution. The data analysis used the interactive model by Miles & Huberman, with triangulation validation to ensure the accuracy and consistency of the findings. The results indicate the presence of gharar in several aspects, such as price uncertainty, quotas, and distribution schedules. Price uncertainty causes subsidized LPG prices to often exceed the Highest Retail Price (HET), while uneven distribution leads to injustice in access for households in need. Violations of the ‘adl principle are evident from the unequal and uneven distribution, which leads to access disparities among low-income households. Based on these findings, it is crucial to digitalize the LPG distribution system to make it more transparent, enhance supervision of distribution practices, and strengthen consumer literacy so they better understand their rights and obligations in accordance with Islamic economic principles. With these measures, uncertainty and injustice in subsidized LPG distribution can be minimized, leading to a more equitable and transparent distribution system.